Fiscal Policy in Indonesia: Analysis of State Budget 2017 in Islamic Economic Perspective - Jaelani, Aan (International Journal of Economics and Financial Issues, 2017)
This study of fiscal policy in State Budget (APBN) 2017 that the task of the Indonesian government to run them to create prosperity for the community. The state budget is prepared using the rules of public economics consisting of state revenues, state expenditures, and budget financing has the posture of the budget, the issues of fiscal policy, and the role of the government in carrying out its functions. With the analysis of Islamic economics, fiscal policy in the State Budget 2017 is the duty of the government to implement the budget for the public welfare with indicators on aspects of religion (religious life), life (justice and security), intellect (education), descent (health and social security family), and treasure (income distribution and access to employment). Keywords: fiscal policy, state budget, welfare, maqashid shariah, Islamic economics JEL Classifications: E62, F52, G18, H61, O23, P43